PERAN NEGARA DALAM MELINDUNGI HAK TENAGA KERJA INDONESIA DI MASA PANDEMI COVID-19 - Yulianto Syahyu (Trunojoyo Madura University, 2023)
It is undeniable that the emergence of the Covid-19 pandemic is unavoidable and has an impact on all lines of life, including the economic sector, as a result, it not only has an impact on the decline in the level of the economy but also has an impact on termination of employment. This article aims to examine the policies taken by the State, in this case the Government and what the government should do in order to protect the rights of Indonesian workers duringithe Covid-19ipandemic. The researchimethod used isinormative juridical by reviewing the applicable laws and regulations. The results of the study indicate that in terms of protection of workers, steps or policies taken by the government are to issue several regulations as firm steps regarding legal protection efforts for workers and their implementation for workers. In addition to regulations and technical rules that are regulated for workersiduring the Covid-19ipandemic, the Government has also issued several policiesito cope withtthe impact of Covid-19, namely in the form of social policies that are expected to be felt directly for the workforce.